Development of a hoverboard / Siti Rafhanah Suwandi and Mohd Fadzli Ismail - Suwandi, Siti Rafhanah; Ismail, Mohd Fadzli (School of Mechanical Engineering, 2023)
Hoverboarding is a mode of personal transportation that allows people to get to their destination quickly without becoming physically tired as they would if they were walking. Walking long distances can be physically exhausting and time-consuming, especially for students who have a tight schedule. The aim of this project is to design and fabricate a hoverboard for students to use on their daily walks to and from class. The hoverboard is designed to be controlled by pedals and powered by DC batteries. When the pedals are pressed or loaded, the engine beneath the platform turns the tires connected to it, and the board naturally balances when people ride it, preventing any mishaps. The constructed hoverboard proved to be an efficient and reliable mode of transportation for students, saving time and energy and providing a convenient alternative to walking. This study recommends introducing the hoverboard to students on their daily walks to and from class to help improve their commuting experience. The hoverboard has the potential to change the way students move around the campus, providing a comfortable and efficient mode of transportation